Cuidado de enfermería en adultos mayores con insuficiencia renal crónica ingresados en el hospital IESS Babahoyo junio -octubre 2023. - Castillo Andrade, Belkys Katherine (2023)
Introduction Chronic kidney failure is a very complicated determinant of health due to its incidence and prevalence over the years. In the last decade, the increase in this disease has doubled, thus causing a problem that affects the entire population. Objective: • Establish nursing care in older adults with chronic renal failure admitted to the Iess Babahoyo hospital June - October 2023 Methodology: The present study is focused on a Field Research through the collection of data that can be applied in the presence of the functions performed by each of the nurses in the care of patients with CKD admitted to the area of internal medicine at the IESS Babahoyo hospital. Results: establishing a grade in the sample of 30 patients with Chronic Kidney Failure (CKD) problems who were admitted to the IESS Hospital of Babahoyo in the period June-October 2023, while all nurses will be taken as a reference. of the different shifts in the internal medicine area. Conclusions: Once this research project is completed, the following conclusions are established based on the statistical data collected during this field research work. Theoretical research shows that the risk factors that are associated with nursing care by health personnel (nursing) towards patients with chronic renal failure who are admitted to the internal medicine area of the Iess Babahoyo hospital in order to improve their quality of life.